Current strategies, perspectives and challenges in management and control of post harvest diseases of papaya - Tan, Guang Heng; Ali, Asgar; Siddiqui, Yasmeen (Elsevier, 2022)
Papaya (Carica papaya) is essential produce specifically in tropical countries due to its rich nutritional and economic benefits, excellent flavours, drug development and industrial processing. This had become a vital source of income for the papaya growing countries by exporting the fresh fruit and processed products in the countries where the demand for tropical fruit is high. However, this climacteric fruit can deteriorate at a higher rate due to severe infections caused by various pathogens that grow at the fruit epiphytically and endophytically during postharvest handling. These postharvest decays are irreversible and cause significant changes in the overall fruit quality and increase the rates of losses during the postharvest chain in the papaya-producing countries including Malaysia. With a better understanding of the causal agents, subsequent control of papaya fruit is applied to delay the disease establishment by different methods. For example, chemical control involved the utilisation of chemicals to disrupt the growth and development of the fungus, while physical control utilises manual alteration on the fruit surrounding for sterilization and delaying the ripening process. Whereas, biological control relied on the naturally found product which can combat the fungal invasion via competition for nutrients, creating protective barriers, induction of PR proteins and resistance. Since synthetic fungicide had been known to have various drawbacks to human health and the environment, many safe and cost-effective alternatives are introduced. However, some of the promising alternatives are only available during the laboratory stage and indicate their potential to be used on-field by optimization and development of novel and safe products. Therefore, this article reviewed different postharvest control strategies that had successfully controlled or could control the growth of the pathogens of papaya, along with their impacts on the fruit quality based on the literature available currently.